PENGEMBANGAN STRATEGI DIGITAL MARKETING BERKELANJUTAN: INTEGRASI MEDIA SOSIAL DAN APLIKASI MOBILE SEBAGAI ALAT KOLABORATIF MASA KINI - Niswa Auliya Lubis; Zuhrinal M. Nawawi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to develop a sustainable digital marketing strategy through the integration of social media and mobile applications as contemporary collaborative tools for Micro, Small, and Medium Enterprises (MSMEs). Using a qualitative approach based on literature review and empirical analysis, the research reveals that the integration of these digital platforms significantly enhances engagement, loyalty, and active collaboration between companies and consumers through co-creation value. Despite substantial challenges such as limited resources, digital competencies, and technical constraints, opportunities for innovation with cutting-edge technologies like artificial intelligence and omnichannel CRM provide avenues for market expansion and digital community strengthening. Best practices including message consistency, creative content, and digital training are key to successful implementation. The long-term impact of this integration drives business growth and sustainability for MSMEs in the Society 5.0 era. This study contributes novel insights by highlighting collaborative aspects and advanced technologies in sustainable digital marketing for MSMEs, while offering strategic recommendations for enhancing digital capacity in Indonesia and other developing countries.